Examining the Practice of Solid Wastes Recycling in Libya - OMRAN, Abdelnaser (Journal of Environmental Management and Tourism, 2016)
Solid waste is one of the major environmental problems in Libya. It plays a significant role in the ability of nature to sustain life within its capacity. Recycling of solid wastes is considered as one the solutions to recover the waste generated. This study aimed to examine the restrictions that hinder residents from practicing recycling. A structured questionnaire was designed to serve as the instrument for the collection of data which was administered on 700 randomly selected in the city of Al-Marj. Out of the 700 questionnaires sent out, only 482 were retrieved representing a response rate of 69%. Based on the findings, it was found that the majority of the residents in the city believed that recycling solid waste is a very important activity; however, their attitude toward this activity was found to be negative. The residents did not recycle nor were they involved in such activities. Most residents do not know how to recycle solid waste; some of them did not even know the items that can be recycled.
Keywords: practices; participation; recycling; solid waste; Libya